Investigating determinants of Bay’ Salam financing product for agricultural sector in the Sultanate of Oman - Ahmed, Umar; Ahmad Fida, Bashir (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study is to investigate the determinants of Bay’ Salam financing product for the agricultural sector in Oman. A survey is conducted using well structured questionnaires to identify the factors that determines viability of Bay Salam financing product for the agricultural sector. The statistical tools used for the analysis are factor analysis and descriptive statistics. The factor analysis results demonstrate that operational costs, profitability and risk mitigation strategies are the most important factors that banks need to take into consideration when financing the agricultural sector using Bay’ Salam. Therefore, we suggest that Islamic banks in Oman should adopt Bay’ Salam as an alternative Islamic product to finance the agricultural sector. Moreover, the Central Bank is encouraged to allow Islamic banks to adopt this product given that it will assist the government in achieving its 2040 vision.